Splenorenal Manifestations of Bartonella henselae Infection in a Pediatric Patient - Taylor Rising; Nicholas Fulton; Pauravi Vasavada (Case Reports in Radiology)
Bartonella henselae is a bacterium which can cause a wide range of clinical manifestations, ranging from fever of unknown origin to a potentially fatal endocarditis. We report a case of Bartonella henselae infection in a pediatric-aged patient following a scratch from a kitten. The patient initially presented with a prolonged fever of unknown origin which was unresponsive to antibiotic treatment. The patient was hospitalized with worsening fevers and night sweat. Subsequent ultrasound imaging demonstrated multiple hypoechoic foci within the spleen. A contrast-enhanced CT of the abdomen and pelvis was also obtained which showed hypoattenuating lesions in the spleen and bilateral kidneys. Bartonella henselae IgG and IgM titers were positive, consistent with an acute Bartonella henselae infection. The patient was discharged with a course of oral rifampin and trimethoprim-sulfamethoxazole, and all symptoms had resolved following two weeks of therapy.